2013
DOI: 10.1186/1748-717x-8-149
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric accuracy and clinical quality of Acuros XB and AAA dose calculation algorithm for stereotactic and conventional lung volumetric modulated arc therapy plans

Abstract: IntroductionThe main aim of the current study was to assess the dosimetric accuracy and clinical quality of volumetric modulated arc therapy (VMAT) plans for stereotactic (stage I) and conventional (stage III) lung cancer treatments planned with Eclipse version 10.0 Anisotropic Analytical Algorithm (AAA) and Acuros XB (AXB) algorithm.MethodsThe dosimetric impact of using AAA instead of AXB, and grid size 2.5 mm instead of 1.0 mm for VMAT treatment plans was evaluated. The clinical plan quality of AXB VMAT was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
102
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 33 publications
10
102
2
Order By: Relevance
“…Kroon et al (10) compared the PDD using AXB for a 6 MV photon beam on a phantom containing the low‐density area and showed that the AXB was acceptably consistent with measurement. In our study, AXB was found to be in better agreement with measurement compared with AAA or PBC in phantoms including low‐ or high‐density areas for a 4 MV photon beam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kroon et al (10) compared the PDD using AXB for a 6 MV photon beam on a phantom containing the low‐density area and showed that the AXB was acceptably consistent with measurement. In our study, AXB was found to be in better agreement with measurement compared with AAA or PBC in phantoms including low‐ or high‐density areas for a 4 MV photon beam.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have been conducted on the clinical impact of AXB for various sites 7 , 10 , 11 . They compared the dose distributions calculated by AXB with those by AAA in IMRT or volumetric‐modulated arc therapy (VMAT) using 6 or 15 MV photon beams for lung cancer or nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…6) show that the achievable agreement is within 5%. This may be due to mixture voxels created at each interface in the phantom and the coarse spacing of the dose grid 35. The mixture voxels consisting of both air and plastic are created along all interfaces between these materials.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a deterministic solution for the Boltzmann equation, unlike the MC approach, where the solution is achieved stochastically. Acuros XB was shown to be more accurate than AAA and CCC in calculating the dose in regions with complex geometries and heterogeneities 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 . Bush et al (10) validated Acuros XB against MC in multi‐slab heterogeneous phantoms with low‐ and high‐density heterogeneities.…”
Section: Introductionmentioning
confidence: 99%